Potential of Aik Bone Protected Forest as an Eco-Tourism Area Based on Structure, Composition and Vegetation Diversity - Mega Safitri; Lalu Japa; I Gde Mertha (Jurnal Biologi Tropis, 2022)
This research was intended to determine whether Aik Bone Protected Forest has potential to be developed as an ecotourism area based on the structure, composition and diversity of vegetation. Because the Aik Bone protected forest area had previously been developed into a tourist destination by surrounding community. But, it has been not success and cannot last long,, because the planning cinditions is bad and the lack of maintenance of the existing facilities. The Aik Bone protected forest is located in the Aik Bukak Village, North Batukliang District, Central Lombok Regency. The type of research was a descriptive quantitative research. The purpose research were to analyze about the density, frequency, dominance and diversity index of vegetation species. The vegetation species found in Aik Bone protection forest were classified into 15 families and with a total of 156 in dividuals/Hectare. Plants species that had the highest important value index at the seedling and sapling category were Caffea canephora. While for pole category is Tabernaemontana sphaerocarpa Blums and thee category Swietenia macophyla King. Species diversity index for seedling, sapling and tree categories was moderate, while pole category was low.